Laparoscopic castration in stallions with two different testicular blood vessels occluding techniques - EL-KHAMARY, A, N,; EL-SHERIF, M. W. (Journal of the Hellenic Veterinary Medical Society, 2019)
Castration of horses is indicated for many reasons and could be performed with variable techniques. Laparoscopic castration is an improved choice. Laparoscopic castrated horses have better cosmetic appearance, return rapidly to normal physical status and have little postoperative complications. The main challenges during laparoscopic castration are obtaining an optimal visualization of the internal inguinal orifices and their content of vas deferens and testicular blood vessels and appropriate occlusion and transaction of the testicular blood vessels to obtain avascular atrophy of the testicles that remains in situ within scrotum. Laparoscopic castration was performed in horses lied in lateral recumbency for better visualization of the target structures and two methods for vascular occlusion were compared. Endo-clipping is effective testicular vessels occluding method and more reliable than bipolar cauterization. Lateral recumbency layout decreased risks of hemodynamic changes during surgery and provided optimal visualization of the surgical field.